2020
DOI: 10.1007/s11695-020-05005-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Obesity Management Services in the United Kingdom (The COMS-UK study)

Abstract: Coronavirus Disease-2019 (COVID-19) has had a severe impact on all aspects of global healthcare delivery. This study aimed to investigate the nationwide impact of the pandemic on obesity management services in the UK in a questionnaire-based survey conducted of professionals involved in the delivery. A total of 168 clinicians took the survey; the majority of which maintained their usual clinical roles and were not redeployed except physicians and nurse specialists. Nearly all (97.8%) elective bariatric surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Similarly, Fresán et al reported that obesity was an independent risk factor for hospitalization and COVID-19 severity, especially in young patients; Peters et al reported that obesity increase the odds for COVID-19 mortality for both genders (Fresán et al, 2020;Peters et al, 2020). Even though some studies identified increased BMI risk on COVID-19 poor outcome among certain groups, such as young people, women or people of black and Asian ethnic backgrounds, it seems that obesity is considered an independent risk factor for poor COVID-19 outcome across all patients groups, and even sometimes preceding the age as the main risk factor for poor prognosis of this novel infection (Caci et al, 2020;Fresán et al, 2020;Magdy Beshbishy et al, 2020;Moussa et al, 2020;Popkin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Fresán et al reported that obesity was an independent risk factor for hospitalization and COVID-19 severity, especially in young patients; Peters et al reported that obesity increase the odds for COVID-19 mortality for both genders (Fresán et al, 2020;Peters et al, 2020). Even though some studies identified increased BMI risk on COVID-19 poor outcome among certain groups, such as young people, women or people of black and Asian ethnic backgrounds, it seems that obesity is considered an independent risk factor for poor COVID-19 outcome across all patients groups, and even sometimes preceding the age as the main risk factor for poor prognosis of this novel infection (Caci et al, 2020;Fresán et al, 2020;Magdy Beshbishy et al, 2020;Moussa et al, 2020;Popkin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Elective surgeries are still being postponed at several centers worldwide to take care of the COVID patients with limited health resources. In the United Kingdom, nearly all elective bariatric surgeries were postponed in April 2020, the peak COVID-19 pandemic [9]. Various other abdominal surgeries, including colorectal surgeries [10,11], solid organ transplants [12], were severely affected in 2020.…”
Section: Impact Of Covid-19 Pandemic On Gastrointestinal Surgical Servicesmentioning
confidence: 99%
“…Frequency of on-site face-to-face obesity management services ( 12 , 13 ) and bariatric surgeries were reduced or canceled during the lockdown period ( 13 , 14 ). This further impacted individuals with obesity who were actively seeking treatment for weight loss, those who were already enrolled in a weight loss program, and patients in post-bariatric operative care.…”
Section: Introductionmentioning
confidence: 99%